‘Komik Indonesia itu Maju’: Tantangan Komikus Underground Indonesia - Tito Imanda (Antropologi Indonesia, 2002)
This paper illustrates the significance of underground comics in Indonesia in the absence of a national comics industry. Underground comics means that its selling is independent of common marketing channels, and the comics usually have non-conventional graphics and narrative style. The author focuses on the life and works of Athonk, an Indonesian independent comics' artist, bypasses conventional modes of marketing and strengthens the global network of independent comics' artists and fans through internet. Fed up with the absurdity of Indonesian cultural and political life, Athonk is consistently creating stories of contestation between the powerful and powerless with cynicism through his amusing characters and language. The author places Athonk in the context of Indonesia art history, and debate between 'high art' and 'low art' that dominates discussion of art in Indonesia. The situation discredits comics as a 'low art' form which makes it still very far from establishing its position. Ironically, public welcome his art and this motivates him to keep working. This article hopefully will give broader picture about Indonesian comics as a potential art form and expression in the future.